Behavioral heuristics and financing decisions in companies - Moscoso Zegarra, Giomar Walter (2023)
Finance, as an area of knowledge derived from the economic sciences, is developed so that the users of the information can make three important decisions for the sustainability of companies. The first one deals with investment decisions, which seek to maximize benefits and minimize costs, which, when compared to the total investment and the cost of resources, should generate added value for the organization. To this end, companies must carefully choose the investment options, selecting those that are most likely to generate a return, always within the level of risk that the shareholder can tolerate and understanding that there is also a level of uncertainty that must be considered when determining the desired profit margins or opportunity cost.The second decision, a variable in this research, deals with the cost of resources and the means by which organizations obtain the cash flows they need to invest in assets. Therefore, when choosing the financial structure that serves as the basis for the development of the business line, decision-makers may find that the cost of obtaining funds, under the figure of "own resources" or equity contribution, is higher than the cash flows that can be obtained in the financial system. This is due to the fact that the risk assumed by the shareholder is greater than that of the lender, and this scenario is reflected in the rates of return required by each of them. Their consolidation, considering such rates, plus the weight that each contribution has within the financial structure, the risk and the opportunity cost, are combined in the determination of the weighted average cost of capital, which becomes the main parameter to measure the effectiveness of the actions implemented within the framework of the "first classic decision of finance".On the financing decisions or how the companies build their capital structures there are several researches, having the origin of the discussion of the problem in the research of (Modigliani, F. & Miller, M. 1958): In much of his formal analysis, the economic theorist has at least tended to side-step the essence of this cost-of-capital problem by proceeding as though physical assets-like bonds-could be regarded as yielding known, sure streams. Given this assumption, the theorist has concluded that the cost of capital to the owners of a firm is simply the rate of interest on bonds; and has derived the familiar proposition that the firm, acting rationally, will tend to push investment to the point where the marginal yield on physical assets is equal to the market rate of interest. This proposition can be shown to follow from either of two criteria of rational decision-making which are equivalent under certainty, namely (1) the maximization of profits and (2) the maximization of market value. (pag. 263)The authors, as the main background for this research, discuss how the correct determination of the cost of capital in companies should be, considering that these will always seek a return at least equitable with the interest rates (return) offered by the market. With this, the aim is to comply with absolute rationality, that is, to seek the maximization of profits and the generation of value for the market. At the end of the research, (Modigliani, F. & Miller, M. 1958), claim to have achieved an operational definition of the cost of capital, that is, they propose the method and variables to be considered in its calculation, but they make an important warning for the present study; that this should always be considered in a rational investment decision making process.It is precisely from this seminal postulate that the relationship between the selection of financial structures and non-rational decisions is sought. In this regard, the research of Simon (1965), which describes the following, is an antecedent: Let me propose a methodological principle to replace Friedman's principle of unreality. I would like to call it continuity of approximations. It consists in that, if the conditions of the real world approximate the assumptions of an ideal type sufficiently well, the derivations on that assumption will be approximately correct. The unreality of the premises is not a virtue of a scientific theory, it is a necessary evil, a concession to the finite computational capacity of the scientist that is tolerable by the principle of continuity of approximation. (p.35).With such reasoning, Simon initiates the debate on how scientific theories establish their premises to predict an event. Premises that, in the author's words, are unreal, but necessary if a result is desired.In this regard, Kahneman, D. (2015) postulates the following:Individuals will always be more sensitive to how an outcome deviates from their "reference level" (the status quo), than to the absolute outcome. When faced with a sequence of decisions under risk, they take each optimizing decision (of gains or losses) without registering the consequences for their wealth as a whole: they seem to be more loss averse, relative to their reference level, than partial to gains of equal amount. (p.126)The reasoning, originally by Simon and later by Kahneman, knows that traditional analysis assumes that natural reactions to risk, such as aversion, propensity or simple neutrality are mostly independent of whether or not cash flows are generated. Therefore, in uncertainty scenarios, individuals are not aware of the effects of the decision, but they are aware of the "reference point" used to shape that decision. Therefore, in a scenario of uncertainty, individuals tend to modify their behavior in the face of gain or loss scenarios, maximizing subjectivity in the face of a negative outcome.